Structure, Physicochemical Properties and Antioxidant Activities of Pectin Obtained from Different Varieties of Potato Residue - Ruiping GAO; Wei TANG; Mingyan LIANG; Wenbin ZHOU; Li WU; Qiaoyu WU; Ruoruo WANG; Jia LIU (Shipin gongye ke-ji)
In this study, pectin was extracted using an acid method from potato residues of four cultivars, including Marco Gaoshan from Enshi, Hubei (HP), red-skinned and yellow-fleshed potatoes from the Yunnan Plateau (YP), russet-skinned potatoes from Dingxi, Gansu (GP), and yellow-skinned and yellow-fleshed potatoes from Rugao, Jiangsu (JP). The extracted pectins were comparatively analyzed in terms of their structural characteristics, physicochemical properties, and antioxidant activities. Results showed that the extraction rates of four pectins followed the order of GP (19.87%)>YP (16.87%)>HP (13.09%)>JP (10.82%). All four pectins were classified as low-ester pectin with the degree of esterification from 23.82% to 41.13%. The monosaccharide composition characterization reveled that the proportion of galactose (46.56%~52.78%) was higher than that of galacturonic acid (31.77%~39.31%), indicating all four pectins were classified as RG-I pectin. In addition, the proportions and branching degrees of the RG-I were arranged in the order of YP>HP>GP>JP. The molecular weights of the pectins followed the order of YP (348.72 kDa)>HP (316.12 kDa)>GP (171.47 kDa) >JP (125.12 kDa). SEM structural observations revealed that HP and YP exhibited relatively regular flake-like structures, while JP presented a densely packed flocculent structure, and GP showed a network-like structure. The viscosity of the pectins followed the order of GP (1356.54 mPa·s)>JP (1079.28 mPa·s)>YP (203.17 mPa·s)>HP (101.82 mPa·s). Notably, the viscosity of GP and JP was significantly higher than those of HP and YP (P<0.05), which was closely related to the molecular weights of GP and JP being much lower than those of HP and YP, as well as the differences in their microstructures. The emulsifying abilities and emulsion stability of the pectins followed the order of YP> HP>GP>JP, which correlated positively with molecular weight and the proportion and branching degree of RG-I structural domains. The antioxidant activity followed the order of JP>GP>HP>YP, which correlated negatively with molecular weight and the proportion and branching degree of RG-I structural domains. This study will provide a theoretical reference for further exploring the gel properties and biological activity of potato pectin.